Effects of Fish Oil Supplementation during the Suckling Period on Auditory Neural Conduction in n-3 Fatty Acid-Deficient Rat Pups - vida rahimi; saeid farahani; Atoosa Saeidpour; Shohre Jalaie; Parvane Mahdi (Iranian Journal of Otorhinolaryngology, 2014)
Abstract Introduction: Omega 3 fatty acid especially in the form of fish oil, has structural and biological role in the body's various systems especially nervous system. Numerous studies have tried to research about it. Auditory is one of the affected systems. Omega 3 deficiency can have devastating effects on the nervous system and auditory. This study aimed to evaluate neural conduction in n-3 fatty acid-deﬁcient rat pups following the supplementation of fish oil consumption during the suckling period Materials and Methods: In this interventional and experimental study, one sources of omega3 fatty acid (fish oil) were fed to rat pups of n-3 PUFA-deficient dams to compare changes in their auditory neural conduction with that of control and n-3 PUFA-deficient groups, using Auditory Brainstem Response (ABR). The parameters of interest were P1, P3, P4 absolute latency, P1-P3, P1-P4 and P3-P4 IPL , P4/P1 amplitude ratio . The rat pups were given oral fish oil, 5 Ml /g weight for 17 days, between the age of 5 and 21 days. Results There were no significant group differences in P1 and P3 absolute latency (p > 0.05). but the result in P4 was significant(P ≤ 0.05) . The n-3 PUFA deficient +vehicle had the most prolonged (the worst) P1-P4 IPL and P3-P4 IPL compared with control and n-3 PUFA deficient + FO groups. There was no significant difference in P1-P4 IPL and P3-P4 IPL between n-3 PUFA deficient + FO and control groups (p > 0.05).There was a significant effect of diet on P1-P4 IPL and P3-P4 IPL between groups (P ≤ 0.05). Conclusion: The results of present study showed the effect of omega3 deficiency on auditory neural structure during pregnancy and lactation period. Additionally, we observed the reduced devastating effects on neural conduction in n-3 fatty acid-deﬁcient rat pups following the supplementation of fish oil during the suckling period